Learning Media Design Innovation of Civic Education: Overcoming Teacher Constraints and Encouraging Student Interest in Learning with Quizwhizzer in the Digital Era in SMPN 13 Medan - Nofryanti N, Satya; Sitanggang, Agnes; Fadly, Ikhsanul; Jamaluddin, Jamaluddin; Yunita, Sri (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This article aims to find out how innovative PPKn learning media designs are in overcoming teacher obstacles and encouraging students' interest in learning with qizwhizzer in the digital era at SMPN 13 Medan. The method used in this research is a qualitative descriptive method. Both primary and secondary data were collected then analyzed and presented descriptively. This journal aims to describe what obstacles teachers have in designing learning media, how teachers implement innovative learning media in the classroom, to find out what factors hinder teachers in designing learning media, and to find out how to implement quizwizzher-based learning media in the classroom. . The analysis findings reveal that in the ever-growing digital era, innovation in learning media, such as the use of QuizWhizzer, has played an important role in supporting Civics education at SMPN 13 Medan. The results of this research show that QuizWhizzer provides an effective solution in overcoming obstacles faced by teachers and encouraging students' interest in learning. Teachers who have adopted QuizWhizzer have experienced significant changes in their ability to teach Civics. They found that using QuizWhizzer allowed them to become more engaged in learning, create engaging material, and adapt their learning approach to students' needs. This, in turn, has increased students' interest in learning.